QUARTZ MEGACRYSTS IN GREECE: MINERALOGY AND ENVIRONMENT OF FORMATION - Maneta, V.; Voudouris, P. (Bulletin of the Geological Society of Greece, 2010)
Quartz megacrysts in Greece are systematically sampled, described and classified with respect to their morphology, solid inclusion mineralogy, and geological conditions of formation. Quartz deposition took place due to reduction in silica solubility in the hydrothermal fluids in favourable geological environments such as: alpine-type fissures close to major detachment faults, skarns and quartz veins crosscutting and generally related to granitoids and, finally, epithermally altered volcanic rocks of Tertiary age. The varieties of coloured crystals (amethyst, smoky quartz, morion, green quartz, rock crystal), the twinning of the crystals, the mineralogy of solid phases included in quartz (rutile, chlorite, sericite, feldspars) as well as the types and forms of the crystals (Tessin habit, Muzo habit, faden quartz, sceptre, window quartz, interrupted crystals, double-terminated crystals, phantom quartz, gwindel quartz, etc.) give important information on the growth mechanisms and the physico-chemical conditions during quartz formation. The quartz crystals found in several localities are gemmy and their potential for use as gemstones should be evaluated.